An Overview of the Growth of Bangladesh's Renewable Energy Sector, Outlining Current Challenges and Future Prospects - Ullah, Aman; Hussain, Md. Naeem; Ahamad, Firoj; Saifullah, Saifullah; Roman, Fahim Al Mahmud (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this review is to develop renewable energy (RE) sectors and overcome any obstacles regarding this in Bangladesh. Bangladesh has been facing energy crisis in all sectors in need of electricity. The techno-economical and policy making challenges are the main barrier of renewable energy sources installment in Bangladesh. But in recent years, Bangladesh has achieved notable progress in the development of its renewable energy industry. Bangladesh produces 723.26 MW of electricity from renewable sources, which include 67.61% solar, 31.80% hydro, and 0.58% wind, biogas, and biomass. Of these, 489 MW are produced by more than 6 million (63, 25, 278) installed solar cells. This assessment offers a thorough examination of the nation's present renewable energy situation, stressing both the fundamental difficulties and noteworthy successes. The research reviews the many renewable energy sources, such as hydropower, biomass, mechanical vibration, wind, and solar electricity, and assesses how much of each the country needs to use. Analyzing the legal and policy environment that governs renewable energy in Bangladesh, the research highlights the necessity of focused measures to remove current obstacles. It talks about how overcoming obstacles and promoting sustainable growth can be accomplished through international cooperation and financial assistance. The research also looks at the socioeconomic effects of renewable energy programs, considering how they may affect employment and electrification in rural areas. The analysis provides an outlook on the prospects of the renewable energy sector in Bangladesh. Emerging technologies, possible market trends, and innovative prospects are covered. To assist stakeholders, investors, and legislators in navigating the shift to a more resilient and sustainable energy future, recommendations are offered. With an emphasis on highlighting successes and outlining challenges, this research provides a thorough analysis of Bangladesh's renewable energy industry. Bangladesh may establish itself as a regional leader in the adoption of renewable energy sources and support international efforts to mitigate climate change by recognizing the obstacles of the present and laying out a plan for future development. This research will help to the researchers and policymakers for making more renewable energy in Bangladesh without facing any difficulties.